2016
DOI: 10.5430/jnep.v7n2p69
|View full text |Cite
|
Sign up to set email alerts
|

Workplace bullying among nurses working in tertiary hospitals in Enugu, southeast Nigeria: Implications for health workers and job performance

Abstract: Background: Workplace bullying among nurses has been identified as a major contributor to poor attitude towards duties, and reduction in overall productivity. This study examined the occurrence and effects of behaviors that constitute workplace bullying among nurses in tertiary hospitals in Enugu, Southeast Nigeria. Methods: Data were collected from 286 nurses working in 4 tertiary hospitals in Enugu State, Southeast, Nigeria, using a modified 22-item Negative Acts Questionnaire (NAQ) for measuring bullying be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
4
15
3
Order By: Relevance
“…The result of present study was agreed with Fountain (2016) (15) who revealed that staff nurses, those nurses who work on medical/surgical units and those who work in non-acute hospital settings had lower levels of work engagement. Conversely, the result of present study was disagreed with, Badran (2019) (37) who revealed that less than two-thirds of the sample had moderate work engagement level.…”
Section: Discussioncontrasting
confidence: 99%
“…The result of present study was agreed with Fountain (2016) (15) who revealed that staff nurses, those nurses who work on medical/surgical units and those who work in non-acute hospital settings had lower levels of work engagement. Conversely, the result of present study was disagreed with, Badran (2019) (37) who revealed that less than two-thirds of the sample had moderate work engagement level.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be noted that most of the studies were published in Asia (39.5%), followed by North America (31.5%). Few publications on the subject were found for South America and Africa, indicating the need for further studies in these localities (16,28) .…”
Section: Discussionmentioning
confidence: 99%
“…Most articles sought to identify the existence of bullying among nursing professionals using specific data collection instruments in the fields of psychology and health care. In this review, we observed a predominance of the Negative Acts Questionnaire Revised (NAQ-R), used in 21 studies (2,10,11,14,(22)(23)(24)(25)(26)28,(33)(34)(35)(36)(37)39,41,44,(46)(47)(48)(49)52) . The original version of this instrument contains 22 items that report negative acts in the work environment and it is widely used in research on bullying (53) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), which often resulted in depression and psychological burnout. In terms of workplace bullying, relational aggression, where a perpetrator uses a relationship to inflict social harm on a victim, is more common among female than male employees (Nwaneri, Onoka, & Onoka, 2016), perhaps because women's sensitivity to their psychosocial surroundings enables them to better identify relational aggression than men (Denton, Prus, & Walter, 2004;Seo, 2010). Also, women experience interpersonal distress relatively easily due to the high value they place on interpersonal relationships (Raskauskas & Stoltz, 2004;Rose, Swenson, Lance, Rose, & Randolph, 2006).…”
Section: Discussionmentioning
confidence: 99%